Accounting for enforcement costs in the spatial allocation of marine zones. Issue 1 (7th August 2014) - Davis, Katrina; Kragt, Marit; Gelcich, Stefan; Schilizzi, Steven; Pannell, David
Abstract Marine fish stocks are in many cases extracted above sustainable levels, but they may be protected through restricted‐use zoning systems. The effectiveness of these systems typically depends on support from coastal fishing communities. High management costs including those of enforcement may, however, deter fishers from supporting marine management. We incorporated enforcement costs into a spatial optimization model that identified how conservation targets can be met while maximizing fishers' revenue. Our model identified the optimal allocation of the study area among different zones: no‐take, territorial user rights for fisheries (TURFs), or open access. The analysis demonstrated that enforcing no‐take and TURF zones incurs a cost, but results in higher species abundance by preventing poaching and overfishing. We analyzed how different enforcement scenarios affected fishers' revenue. Fisher revenue was approximately 50% higher when territorial user rights were enforced than when they were not. The model preferentially allocated area to the enforced‐TURF zone over other zones, demonstrating that the financial benefits of enforcement (derived from higher species abundance) exceeded the costs. These findings were robust to increases in enforcement costs but sensitive to changes in species' market price. We also found that revenue under the existing zoning regime in the study area was 13–30% lower than under an optimal solution. Our results highlight the importance of accounting for both the benefits and costs of enforcement in marine conservation, particularly when incurred by fishers. Justificación de los Costos de Aplicación en la Asignación Espacial de Zonas Marinas